2021
DOI: 10.1111/cts.12908
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and Immunological Dysregulation: Can Autoantibodies be Useful?

Abstract: Coronavirus disease 2019 (COVID-19) is often associated with interstitial pneumonia. However, there is insufficient knowledge on the presence of autoimmune serological markers in patients with COVID-19. We analyzed the presence and role of autoantibodies in patients with COVID-19-associated pneumonia. We prospectively studied 33 consecutive patients with COVID-19, 31 (94%) of whom had interstitial pneumonia, and 25 age-and sex-matched patients with fever and/or pneumonia with etiologies other than COVID-19 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
166
4
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(192 citation statements)
references
References 29 publications
13
166
4
9
Order By: Relevance
“…Several reports have shown diverse prevalence of autoantibodies. The most reported comprise the antiphospholipid antibodies, and ANAs [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. Herein, we found that hospitalized patients with COVID-19 exhibited higher frequency of latent phospholipid, rheumatic and thyroid autoimmunity when compared with pre-pandemic controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown diverse prevalence of autoantibodies. The most reported comprise the antiphospholipid antibodies, and ANAs [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. Herein, we found that hospitalized patients with COVID-19 exhibited higher frequency of latent phospholipid, rheumatic and thyroid autoimmunity when compared with pre-pandemic controls.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most intriguing phenomena of COVID-19 is the presence of autoimmunity. Indeed, a) autoimmune diseases (ADs) have been associated with the disease, in particular Guillain-Barré syndrome, autoimmune cytopenia, and antiphospholipid syndrome [ 1 ]; b) the presence of several autoantibodies has been confirmed [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] ], and c) autoantibodies against cytokines [ 15 ], and even against angiotensin-converting enzyme 2 (ACE-2) [ 16 ], the receptor for SARS-CoV-2, have been observed and associated with severity of disease.…”
Section: Introductionmentioning
confidence: 99%
“…And moreover, the outcome of ANAs positive patients (3 patients in ICU and 2 patients death) were worse than that of the autoantibody negative patients (all alive) [ 5 ]. Third, Pascolini S and colleagues found that 11 patients were positive (33.3%) for ANAs in 33 consecutive patients with COVID-19 [ 6 ]. And moreover, the outcome of ANAs positive patients were worse than ANA negative patients: the death rate of ANAs positive patients were 36.4% (4 death among 11 ANAs positive patients), while the death rate of ANAs negative patients were 13.6% (3 death among 22 ANAs negative patients).…”
mentioning
confidence: 99%
“…The aPL are including anticardiolipin (aCL), anti-beta-2 glycoprotein I (aβ2GPI), anti-phosphatidylserine/prothrombin (aPS/PT) and lupus anticoagulant (LA). Nine studies that have tested the aPL in COVID-19 were reviewed ( Table 2 ) [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ]. These studies showed that: aPL is frequent in COVID-19 patients.…”
mentioning
confidence: 99%
“…A report from Greece demonstrated that the positive rate of ANA was 34.5% in hospitalized patients 10 . In Italy, 34 COVID-19 cases were analyzed, and the detection rate of ANA was 35.3% 8,9 . Apart from those studies, a report from Japan, one of two (50%) severe covid-19 cases were found ANA positive 7 .…”
Section: Discussionmentioning
confidence: 99%